2021
DOI: 10.22271/chemi.2021.v9.i1s.11403
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pyriproxifen 10% EW against sucking insect pest population in cotton

Abstract: An investigation was carried out at AICRP on cotton scheme, Chamarajanagar, Karnataka during kharif season of 2016-17 and 2017-18 to evaluate the bio-efficacy of pyriproxifen 10% EW against sucking insect pests of cotton viz., whitefly (Bemisia tabaci Genn.), aphids (Aphis gossypii Glover), thrips (Thrips tabaci Lind), and leafhopper (Amrasca bigutulla bigutulla Ishida). The study indicated that spraying of pyriproxifen 10% EW @ 200 g.a.i/ha has recorded significantly higher seed cotton yield (19.43 q/ha) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
3
1
0
Order By: Relevance
“…The treatment of NSKE 5% showed moderate effect, whereas, diflubenzuron 25%WP + NSKE 5% and diflubenzuron 25%WP were the least effective. These findings are in agreement with those of Shivaray et al (2021) on the effectiveness of pyriproxyfen 10%EC and buprofezin 25%SC; and those of Sahar (2019) under laboratory and field experiments. Thumar et al (2018) observed pyriproxyfen 10% EC @ 1000 ml/ ha as effective, whereas, Choudhary and Singh (2015) found three sprays of pyriproxyfen at 10 days interval as effective.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The treatment of NSKE 5% showed moderate effect, whereas, diflubenzuron 25%WP + NSKE 5% and diflubenzuron 25%WP were the least effective. These findings are in agreement with those of Shivaray et al (2021) on the effectiveness of pyriproxyfen 10%EC and buprofezin 25%SC; and those of Sahar (2019) under laboratory and field experiments. Thumar et al (2018) observed pyriproxyfen 10% EC @ 1000 ml/ ha as effective, whereas, Choudhary and Singh (2015) found three sprays of pyriproxyfen at 10 days interval as effective.…”
Section: Resultssupporting
confidence: 92%
“…The cumulative means also led the observation that buprofezin 25%SC is superior against T. tabaci (4.60/ leaf) found at par with pyriproxyfen 10%EC, buprofezin 25%SC + NSKE 5%, pyriproxyfen 10%EC + NSKE 5% and NSKE 5% (5.44, 5.50, 5.89 and 6.35 thrips/ leaf, respectively). These results are in tune with those of Shivaray et al (2021) with pyriproxyfen 10%EC and buprofezin 25%SC. Binu and Bhede (2019) reported buprofezin 25%SC as effective.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…@ 250 ml/ha was found the most effective to reduce the whitefly, B. tabaci population in chili crop during kharif, 2016 and 2017. Swathi et al, (2018) and Navi et al, (2021) concluded that the study indicated that spraying of pyriproxyfen 10% EW @ 200 g.a.i/ha has recorded significantly higher seed cotton yield (19.43 q/ha) with a maximum per cent reduction in whiteflies (95.28%), aphids (90.04%), thrips (98.78%) and leafhoppers (94.40%), respectively. Suman et al, (2021) revealed that result revealed that afidopyropen 50 g/l DC @ 600 ml/ha was found to be most effective against jassid, aphid and whitefly.…”
Section: Resultsmentioning
confidence: 99%